Statystyczny pomiar innowacyjności w krajach Unii Europejskiej - Markowska, Małgorzata (Statistical Measurement of Innovation in the European Union Countries, 2006)
The study presents measurement tools used for the assessment of innovation in the European Union countries. The presented diversification of countries with regard to human capital for innovation, creating new knowledge and innovation financing became the basis for grouping the EU countries into similar classes with regard to the level of measuring instruments in each of the presented blocks.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Ekonometria (16); 2006; nr 1100, s. 110-120